Take the 2-minute tour ×
Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. It's 100% free, no registration required.

I have 2 coordinate systems which move along $x,x'$ axis.

I have derived a Lorentz transformation for an $x$ component of momentum, which is one part of an 4-momentum vector $p_\mu$. This is my derivation:

$$ \scriptsize \begin{split} p_x &= mv_x \gamma(v_x)\\ p_x &= \frac{m (v_x'+u)}{\left(1+v_x' \frac{u}{c^2}\right) \sqrt{1 - \left(v_x' + u \right)^2 / c^2 \left( 1+ v_x' \frac{u}{c^2} \right)^2}} \\ p_x &= \frac{m (v_x'+u) \left( 1+ v_x' \frac{u}{c^2} \right)}{\left(1+v_x' \frac{u}{c^2}\right) \sqrt{\left[c^2 \left( 1+ v_x' \frac{u}{c^2} \right)^2 - \left(v_x' + u \right)^2 \right] / c^2 }} \\ p_x &= \frac{m (v_x'+u)}{\sqrt{\left[c^2 \left( 1+ v_x' \frac{u}{c^2} \right)^2 - \left(v_x' + u \right)^2 \right] / c^2 }} \\ p_x &= \frac{m (v_x'+u)}{\sqrt{\left[c^2 \left( 1+ 2 v_x' \frac{u}{c^2} + v_x'^2 \frac{u^2}{c^4} \right) - v_x'^2 - 2 v_x' u - u^2 \right] / c^2 }} \\ p_x &= \frac{mv_x'+mu}{\sqrt{\left[c^2 + 2 v_x'u + v_x'^2 \frac{u^2}{c^2} - v_x'^2 - 2 v_x' u - u^2 \right] / c^2 }} \\ p_x &= \frac{mv_x'+mu}{\sqrt{\left[c^2 + v_x'^2 \frac{u^2}{c^2} - v_x'^2 - u^2 \right] / c^2 }} \\ p_x &= \frac{mv_x'+mu}{\sqrt{1 + v_x'^2 \frac{u^2}{c^4} - \frac{v_x'^2}{c^2} - \frac{u^2}{c^2} }} \\ p_x &= \frac{mv_x'+mu}{\sqrt{\left(1 - \frac{u^2}{c^2}\right) \left(1-\frac{v_x'^2}{c^2} \right)}} \\ p_x &= \gamma \left[mv_x' \gamma(v_x') + mu \gamma(v_x') \right] \\ p_x &= \gamma \left[mv_x' \gamma(v_x') + \frac{mc^2 \gamma(v_x') u}{c^2} \right] \\ p_x &= \gamma \left[p_x' + \frac{W'}{c^2} u\right] \end{split} $$

I tried to derive Lorentz transformation for momentum also in $y$ direction, but i can't seem to get relation $p_y=p_y'$ because in the end i can't get rid of $2v_x'\frac{u}{c^2}$ and $\frac{v_y'^2}{c^2}$. Here is my attempt.

$$ \scriptsize \begin{split} p_y &= m v_y \gamma(v_y)\\ p_y &= \frac{m v_y'}{\gamma \left(1 + v_x' \frac{u}{c^2}\right) \sqrt{1 - v_y'^2/c^2\left( 1 + v_x' \frac{u}{c^2} \right)^2}}\\ p_y &= \frac{m v_y' \left( 1 + v_x' \frac{u}{c^2} \right)}{\gamma \left(1 + v_x' \frac{u}{c^2}\right) \sqrt{\left[c^2\left( 1 + v_x' \frac{u}{c^2} \right)^2 - v_y'^2\right]/c^2}}\\ p_y &= \frac{m v_y'}{\gamma \sqrt{\left[c^2\left( 1 + v_x' \frac{u}{c^2} \right)^2 - v_y'^2\right]/c^2}}\\ p_y &= \frac{m v_y'}{\gamma \sqrt{\left[c^2\left( 1 + 2 v_x' \frac{u}{c^2} + v_x'^2 \frac{u^2}{c^4}\right) - v_y'^2\right]/c^2}}\\ p_y &= \frac{m v_y'}{\gamma \sqrt{\left[c^2 + 2 v_x' u + v_x'^2 \frac{u^2}{c^2} - v_y'^2\right]/c^2}}\\ p_y &= \frac{m v_y'}{\gamma \sqrt{1 + 2 v_x' \frac{u}{c^2} + v_x'^2 \frac{u^2}{c^4} - \frac{v_y'^2}{c^2}}}\\ \end{split} $$

This is where it ends for me and I would need someone to point me the way and show me, how i can i get $p_y = p_y'$? I know I am very close.

share|improve this question
    
$p_{y}=p'_{y}$ only if $u=u_{x}$ and $v_{y}=0$ –  TMS Dec 4 '12 at 13:57
1  
I stated this at the beginning. –  71GA Dec 6 '12 at 22:54
1  
This is honestly a pretty laborious way of doing things. Is there a reason you're avoiding just using the Lorentz transformations (which make the result obvious)? Also, you write $p_y = m v_y \gamma(v_y)$, but $\gamma$ depends on the total velocity $v$, not just the y-component. –  Muphrid Dec 6 '12 at 23:28
    
@Muphrid, you could suggest an alternative in an answer. –  Magpie Dec 7 '12 at 7:04
    
@Muphid It is $p=mv \gamma(v)$ in general. This is what i am sure of. But isn't it like this $p=mv_x \gamma(v_x)$ (gamma is a function of a speed which stands next to $m$) for a component? Was i just lucky above to sucessfully derive first equation i.e. for $p_x$? I mean lucky because i should have used $\gamma(v)$ but i used $\gamma(v_x)$. But because $v_x$ is the whole speed it worked out for $x$ direction. It is not working for $y$ direction because $v_y$ isn't the whole speed. It is actually zero. So i should use $p_y = m v_y \gamma(v_x)$? –  71GA Dec 7 '12 at 8:43

1 Answer 1

up vote 1 down vote accepted

Well this is how $p_y$ part of a four-momentum is put together.

\begin{equation} \scriptsize \begin{split} p &= m v \gamma(v)\\ &\Downarrow\\ p_y &= m v_y \gamma(v) = m v_y \gamma \left( \sqrt{v_x^2 + v_y^2 + v_z^2}\right) = m v_y \gamma \left( \sqrt{v_x^2 + 0 + 0}\right) = m v_y \gamma(v_x) =\\ &= \frac{m v_y'}{\gamma \left(1 + v_x' \frac{u}{c^2}\right) \sqrt{1 - \frac{\left(v_y' + u\right)^2}{c^2 \left(1 + v_x' \frac{u}{c^2}\right)^2}}} = \frac{mv_y'}{\gamma \left(1 + v_x' \frac{u}{c^2}\right) \sqrt{\frac{c^2 \left(1 + v_x' \frac{u}{c^2}\right)^2 - \left(v_x' + u\right)^2}{c^2 \left(1 + v_x' \frac{u}{c^2}\right)^2}}}=\\ &= \frac{mv_y' \left(1 + v_x' \frac{u}{c^2}\right)}{\gamma \left(1 + v_x' \frac{u}{c^2}\right) \sqrt{\left[c^2 \left(1 + v_x' \frac{u}{c^2}\right)^2 - \left(v_x' + u\right)^2\right] / c^2}} = \frac{mv_y'}{\gamma \sqrt{\left[c^2 \left(1 + v_x' \frac{u}{c^2}\right)^2 - \left(v_x' + u\right)^2\right] / c^2}}=\\ &= \frac{mv_y'}{\gamma \sqrt{\left[c^2 \left(1 + 2 v_x' \frac{u}{c^2} + {v_x'}^2 \frac{u^2}{c^4}\right) - {v_x'}^2 - 2 {v_x'}u - u^2\right] / c^2}}=\\ & = \frac{mv_y'}{\gamma \sqrt{\left[c^2 + 2 v_x' u + {v_x'}^2 \frac{u^2}{c^2} - {v_x'}^2 - 2 {v_x'}u - u^2\right] / c^2}}= \frac{mv_y'}{\gamma \sqrt{\left[c^2 + {v_x'}^2 \frac{u^2}{c^2} - {v_x'}^2 - u^2\right] / c^2}}=\\ & = \frac{mv_y'}{\gamma \sqrt{1 + {v_x'}^2 \frac{u^2}{c^4} - \frac{{v_x'}^2}{c^2} - \frac{u^2}{c^2}}}= \frac{mv_y'}{\gamma \sqrt{\left(1 - \frac{u^2}{c^4}\right) \left(1-\frac{{v_x'}^2}{c^2}\right)}}= mv_y' \gamma(v_x')\\ \end{split} \end{equation}

In our case $v_x' = v'$ and we can modify last part of this big equation so that we get:

\begin{equation} \scriptsize \begin{split} p_y= mv_y' \gamma(v')\\ \end{split} \end{equation}

Now we can see Lorentz tr. and reverse Lorentz tr. which are:

\begin{equation} \scriptsize \begin{split} &\boxed{p_y=p_y'} ~~~\boxed{p_y'=p_y}\\ \end{split} \end{equation}

share|improve this answer
    
nice work! I saw some people suggest above that this was the long way of doing things. I would like them to show what they are if that is the case, too. –  Magpie Dec 10 '12 at 18:15
    
This is very clear and i used only simple math. Now it is easy to put together 4-momentum. What i have to do is only put equations for $W$, $p_x$, $p_y$ and $p_z$ one above the other and make a matrix form from which i can see Lorentz matrix $\Lambda$. –  71GA Dec 10 '12 at 20:11
1  
My momentum 4 vector is still sketchy to judge but I don't understand why someone would say there's a better way and not show it. –  Magpie Dec 10 '12 at 22:37

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.